Distribution patterns and foraging ground productivity determine clutch size in Mediterranean loggerhead turtles - Cardona, Luis (2014)
Loggerhead turtles Caretta caretta use a wide variety of foraging strategies, and some populations forage in sub-optimal habitats. Different foraging strategies may not be equiva- lent in terms of fitness and may result in differences in adult body size and clutch size among populations. Accordingly, we tested whether differences in clutch size among rookeries in the Mediterranean Sea are related to differential use of foraging grounds of contrasting productivity. Stable isotope ratios of carbon and nitrogen of turtle hatchlings from 8 Mediterranean rookeries were used to characterise the foraging grounds of their mothers. Clutch size was also studied in each rookery to assess reproductive output linked to foraging ground productivity. According to stable isotope ratios, most of the females nesting in the considered rookeries foraged in the southern Ion- ian Sea. The highly productive Adriatic/northern Ionian Sea region was mainly used by females nesting in western Greece. The explanation for these patterns might be linked to water circulation patterns and drifting trajectories followed during developmental migrations, which might determine individual knowledge on the location of productive foraging patches. Average clutch size in each rookery was positively correlated to the proportion of females accessing highly productive areas such as the Adriatic/northern Ionian Sea. This has a strong influence on reproductive out-put, and hence females using the most productive foraging grounds had the largest clutch sizes.